Love is a losing game: power and exploitation in romantic relationships. Issue 3 (2nd September 2017) - Gregoratto, Federica
Abstract: The article elaborates an account of exploitation in romantic love relationships. As a starting point, I borrow Vrousalis' analytical Marxist definition of economic exploitation under capitalism. Second, I briefly discuss Federici's conception of capitalist exploitation of women's labour in the family and in the romantic couple. I introduce and discuss, then, Jónasdóttir's theory of 'love power', which currently counts as the most elaborated critique of exploitation affecting sexual love. I proceed to sketch out my own account, according to which love power is not extracted or appropriated, as Jónasdóttir puts it, but rather suffocated as result of what I call 'romantic exploitation'. In this view, lovers' positions of vulnerability and power over, that may give rise to exploitation, are brought about by an intersection of norms defining and regulating notions of romance, gender, race, labour, etc.